A metrological atomic force microscope system. (18th March 2021) - Wu, Yiting; Wirthmann, Elisa; Klöpzig, Ute; Hausotte, Tino
Abstract: A new metrological atomic force microscope (MAFM) with combined deflection detection system that comprises a homodyne interferometer and an optical beam deflection measuring system are presented. The combination allows the simultaneous three-dimensional detection of position, bending and torsion of the cantilever. Two wedge plates with a wedge angle of 0.5° have been integrated to reduce the disturbing interferences. The new measuring system uses two tiltable plane mirrors and a shiftable focus lens to adjust the direction of the focused laser beam and the position of the focus. The integration of the MAFM head in a nanomeasuring machine (NMM-1) creates the possibility of traceable dimensional measurements over a large range of 25 mm × 25 mm × 5 mm with sub-nanometre resolution. This paper introduces its setup, realisation and metrological properties, such as stability of the characteristic curves, noise level and combined measurement uncertainty. Finally, exemplary measurement results are presented.